Infecciones en las vías urinarias y sus consecuencias en mujeres embarazadas del Hospital Básico de Baba del periodo octubre 2019- marzo 2020. - Montero Baidal, Jessenia Rosario (2020)
Introduction: Urinary tract infections are a cause of morbidity and mortality at the maternal and fetal level, for this reason a study was carried out with a descriptive, qualitative-quantitative, and retrospective approach in the Basic hospital of Baba in the period October 2019 to March 2020 with the objective of designing a participation strategy to prevent urinary tract infections in pregnant women. Course objective: To analyze the main urinary tract infections and their consequences in pregnant women who are treated at the basic baba hospital of the October 2019-March 2020 period by reviewing medical records to improve the quality of life, avoiding future complications. Methodology: It is a retrospective, descriptive, analytical study. 178 medical records of pregnant patients with a diagnosis of Urinary Tract Infection that were treated at the External Consultation and Gynecology of the Baba Basic Hospital of the Province of the Rivers from October 2019 to March 2020 were reviewed. Results: Of the 75 pregnant women diagnosed with urinary tract infection, the following results were obtained: the prevalence of this pathology was (43%) of the total number of patients, the main form of presentation was asymptomatic bacteriuria (60%) and The main consequence was the threat of pre-term delivery (16%). Conclusions: The incidence of urinary tract infections is high, due to their education and socio-economic problems, taking first place among the morbidity and mortality of pregnant women in 43%.